PELATIHAN “HOW TO WRITE A WINNING SCHOLARSHIP ESSAY” DI SMAK TUNAS BANGSA LIPPO CIKARANG - Rosari, Maria Dewi (LPPM Universitas Islam 45 Bekasi, 2024)
The ability to write essays and speak English is the main qualification in the competition for scholarships and further study opportunities in the era of globalization. SMAK Tunas Bangsa Lippo Cikarang realizes the importance of this, especially for class XII students. In Indonesia, the increasing number of scholarship offers from the government and non-government organizations adds to the complexity of competition. However, not all applicants are successful due to inadequate essay writing and English skills. The